ChemInform Abstract: Interplay of Structure and Dynamics in Functional Macromolecular and Supramolecular Systems as Revealed by Magnetic Resonance Spectroscopy. Issue 12 (March 2016) - Hansen, Michael Ryan; Graf, Robert; Spiess, Hans Wolfgang
Abstract: Review: 356 refs.